Development of liquid milk replacer for rearing early weaned piglets - K. Roopa; R. Karunakaran; D.Balasubramanyam; H. Gopi; L.Radhakrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A 28 day feeding trial was conducted to assess the effect of liquid milk replacer on the growth performance of early weaned piglets. Forty piglets (average birth weight 1.18 ± 0.01 kg) of 14 days of age were selected and grouped into five treatments groups viz (control, unweaned), T1,T2,T3,T4 and T5 and fed with liquid milk replacer type I, type II, type III and type IV, respectively. This study revealed that piglets supplemented with liquid milk replacer type I (T2) had comparable body weight gain (5.95 ± 0.08 kg ) compared to control (5.77 ± 0.28 kg) and T3 , T4 and T5 had significantly lower weight gain than T2 and control piglets.